Electrospray deposited fibronectin retains the ability to promote cell adhesion. - Martyn, S; Heywood, H; Rockett, P; Paine, MD; Wang, M; Dobson, P; Sheard, S; Lee, D; Stark, J (2011)
Scaffolds for tissue engineering require the correct biochemical cues if the seeded cells are to migrate into the scaffold and proliferate. For complex tissues this would require precise patterning of the scaffold structure with the particular biochemical cue required at each location on the scaffold. Electrospray enables the deposition of a wide number of biomolecules onto surfaces and can be used for precise patterning. We assessed the functionality of a key cell-adhesion molecule, fibronectin, after depositing it onto a surface using the electrospray technique. The addition of polypropylene glycol allowed a stable spray to be obtained from solutions with a range of fibronectin concentrations. Immunoassay tests showed that the amount of fibronectin retained on the surface was proportional to that sprayed from the solution. Increasing the surface density of fibronectin deposited onto silicon surfaces enhanced fibroblast attachment. The fibronectin thus appears to have retained its cell attachment functionality after undergoing the electrospray process. Since recent advances allow electrospray to pattern material from solution with micrometre accuracy this may allow materials to be biologically functionalized on a similar scale.